The HAAPI (Home Arm Assistance Progression Initiative) Trial: A Novel Robotics Delivery Approach in Stroke Rehabilitation. (November 2015) - Wolf, Steven L.; Sahu, Komal; Bay, R. Curtis; Buchanan, Sharon; Reiss, Aimee; Linder, Susan; Rosenfeldt, Anson; Alberts, Jay
Background. Geographical location, socioeconomic status, and logistics surrounding transportation impede access of poststroke individuals to comprehensive rehabilitative services. Robotic therapy may enhance telerehabilitation by delivering consistent and state-of-the art therapy while allowing remote monitoring and adjusting therapy for underserved populations. The Hand Mentor Pro (HMP) was incorporated within a home exercise program (HEP) to improve upper-extremity (UE) functional capabilities poststroke. Objective. To determine the efficacy of a home-based telemonitored robotic-assisted therapy as part of a HEP compared with a dose-matched HEP-only intervention among individuals less than 6 months poststroke and characterized as underserved. Methods. In this prospective, single-blinded, multisite, randomized controlled trial, 99 hemiparetic participants with limited access to UE rehabilitation were randomized to either (1) the experimental group, which received combined HEP and HMP for 3 h/d ×5 days ×8 weeks, or (2) the control group, which received HEP only at an identical dosage. Weekly communication between the supervising therapist and participant promoted compliance and progression of the HEP and HMP prescription. The Action Research Arm Test and Wolf Motor Function Test along with the Fugl-Meyer Assessment (UE) were primary and secondary outcome measures, respectively, undertaken before and after the interventions. Results. Both groups demonstrated improvement across all UE outcomes. Conclusions . Robotic + HEP and HEP only were both effectively delivered remotely. There was no difference between groups in change in motor function over time. Additional research is necessary to determine the appropriate dosage of HMP and HEP.